THE EFFECTS OF THE DIGITAL REVOLUTION ON AUDITING AND AUDITORS : DO WE NEED AUDITORS IN THE FUTURE? - Hautala, Aleksi (fi=Turun yliopisto|en=University of Turku|, 2018)
The objective of this paper is to shed light on the relationship between digitalization and auditing. In particular, the aim is to discover the implications of digitalization for the everyday work of the auditor. The study examines the current situation in auditing, but also employs a forward-looking orientation. Thus, another objective of this paper is to analyze possible future implications caused by digitalization. This paper uses a mixed-method –methodology, including a survey (a quantitative element) and interviews (a qualitative element). The survey produced a total of 32 usable responses and three interviews were held with professional auditors, with the total duration of the interviews being approximately 90 minutes. The evidence of this study points out that an experience gap in auditing might emerge because of digitalization. The experience gap might arise when technology (primarily AI-based solutions) advance to a level where the technology can replace humans in basic auditing tasks. This, in turn, decreases the open trainee positions in audit firms, thus making it difficult for the fresh auditing graduates to obtain relevant work experience. The findings of this study also imply that the competitive forces in the auditing business might be heavily affected because of digitalization, as there is a threat of new entrants in the business. Furthermore, the findings also suggest that high-end ICT has not yet been utilized in auditing. For instance, the importance of continuous auditing, Big Data and Artificial Intelligence seems to be still relatively low, even though some of the previous auditing research suggests rather the opposite. A potential bias among the interviewees and survey respondents might affect the generalizability of the results. The interviewees and survey respondents may have given answers, that present them in a more positive light than would be realistical. In addition, the number of survey responses was low (n=32).